Export performance and structure after 1980 - Gün, Saim Murat. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1987., 1987)
The main purpose of this study is to examine the results of the new stability program which was put into force in January 1980. In this study, answers are sought about the problems of our exportation, the reason for the firms not exporting, and the qualifications discriminating the firms who do and who do not export., The sources of information in this study are collected thru literature survey and telephone interviews with the managers of some firms. It is serious that managers of some non-exporting firms who have achieved to be among the first "500 industrial firms" of Turkey as to the year 1985 said that they could be defeated as a result of competition with domestic and foreign firms as the reason for not exporting. Added value and the net total assets of the firms come first among the factors discriminating firms who do and who do not export. It is hoped that the study will stimulate further research on the topic and will provide some insights for motivating non-exporting firms.
Keywords: Exports -- Turkey.